PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI MALI TAHUN 2017-2021 - Daffa Irfanov Kenedi; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This study examines problems regarding the food security crisis experienced by the State of Mali and describes the role of the World Food Program in its efforts to overcome the food security crisis that occurred. The food crisis is a process of decreasing food intake and nutrition in society. The causes of food security in Mali are interrelated, and include poverty, inadequate supply and political instability, conflict, climate change. The problem of food security is exacerbated by political instability, which disrupts food distribution channels and cuts off access to distribution. This study uses a qualitative method that is descriptive. This research was conducted by collecting data in the form of analytical documents. Information retrieval techniques in qualitative research can be divided into literature and literature. In evaluating the role and finding the root of the problem in this study, the theory of International Organizations and the concept of Food Security are used. The result of this research is that through the programs implemented, the World Food Program strives in its efforts to eradicate the food crisis that occurred in Mali and the ultimate goal is that the implemented program can help ease the burden and revive the life of the Malian people so that they return to normal and rise from poverty. food crisis. Keywords: Program, WFP, Food crisis, Mali